2021
DOI: 10.31234/osf.io/cbksd
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Steering is initiated based on error accumulation

Abstract: Vehicle control by humans is possible because the central nervous system is capable of using visual information to produce complex sensorimotor actions. Drivers must monitor errors and initiate steering corrections of appropriate magnitude and timing to maintain a safe lane position. The perceptual mechanisms determining how a driver processes visual information and initiates steering corrections remain unclear. Previous research suggests two potential alternative mechanisms for responding to errors: (i) perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(15 citation statements)
references
References 45 publications
3
12
0
Order By: Relevance
“…This allowed the paradigm to directly exploit the key theoretical differences between Threshold and Accumulator frameworks: how a perceptual signal builds over time. Goodridge et al (2022) found that the timing and magnitude of steering behaviours were in line with Accumulator predicted responses. Drivers did not respond based 7 upon time-independent thresholds, rather they altered their response to the rate at which the perceived control error developed.…”
Section: Introductionsupporting
confidence: 53%
See 4 more Smart Citations
“…This allowed the paradigm to directly exploit the key theoretical differences between Threshold and Accumulator frameworks: how a perceptual signal builds over time. Goodridge et al (2022) found that the timing and magnitude of steering behaviours were in line with Accumulator predicted responses. Drivers did not respond based 7 upon time-independent thresholds, rather they altered their response to the rate at which the perceived control error developed.…”
Section: Introductionsupporting
confidence: 53%
“…Two alternative frameworks -Threshold and Accumulatorhave been proposed as mechanisms that could describe the intermittency involved in steering. Whilst previous research has demonstrated that steering toward straight road-line targets is best explained via an Accumulator framework (Goodridge et al, 2022), aspects of the experimental design (discussed in more detail later) may have made it more likely that people would accumulate perceptual information rather than rely upon fixed time independent thresholds. Therefore a specific aim of this manuscript was to build upon the work conducted by Goodridge et al (2022) to investigate whether Accumulator-predicted steering responses translate to a more general context where the optical information presented to drivers is more closely aligned to that experienced during real-world locomotor settings (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations